Enhancing Oil Production Rate by Well Type Conversion in an Iraqi Field - Al-Hussein Altaher; Maha Hamoudi; Ghassan Abdul-Majeed; Faleh Almahdawi (Iraqi Geological Journal, 2024)
Horizontal wells have been drilled worldwide for the past decades, mainly to increase well’s deliverability. Many vertical wells have been converted to horizontal wells. Only some of them were successful in increasing the oil production rate as expected. In this study, a vertical well (V1) in Kirkuk field was studied and converted to a designed horizontal well (H1) to increase the productivity. PROSPER software was used to model both wells. H1 was designed with well horizontal lengths of 152, 305, 457, and 610 m, and permeability ratios of 0.1, 0.2, 0.4, 0.7 and 1.0. A developed correlation for calculating well construction cost, along with Questor software, were used to perform the economic analysis. It was found that the highest productivity index and production rate ratios were 5.2 and 2.41, respectively. Reservoir pay thickness and permeability ratio are the main parameters in determining the minimum feasible horizontal well length. Reservoir pressure and water cut were found to be the most sensitive parameters in both wells. The net profit generated by a horizontal well with length of 610 m and permeability ratio of 0.2 is 1.9 folds the net profit generated by a vertical well, in three years.